La diaspora andalouse et le commerce des ports maghrébins (xie-xve siècle) - Dominique Valérian (Les Cahiers de Framespa)
In a Mediterranean trade largely controlled by European Christian merchants from the 12th century onwards, the Andalusians –Muslims, but also Jews– were an exception. This is due to a long tradition of commerce in the Muslim world, but also to the Reconquista, which forced large groups of Andalusians to emigrate to the sultanate of Granada and to the Maghreb, and even to the Middle East, especially Egypt. This exile created a very effective network, connecting people who had remained in the Christian kingdoms to those who had settled in the Muslim ports. The skills of the Andalusians, notably in administration and finance, gave them the opportunity to gain political influence and a privileged position in Customs and at the Court. Their traditions of commerce, and their knowledge of Christian commercial practices and languages were also very important assets, which made of them key intermediaries in the intercultural relations in the Mediterranean.